2003
DOI: 10.1114/1.1574027
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Three-Dimensional Finite Element Model for Carpal Load Transmission in a Static Neutral Posture

Abstract: A three-dimensional developmental finite element model has been created to analyze load transmission pathways in the constrained carpus during static compressive loading. The bone geometry was extracted from an in vivo computed tomography scan using a combination of commercial and proprietary software. The complete geometry, including bone, cartilage, and ligament tissues, was compiled using a commercial finite element program. This model extends the state of biomechanical modeling by being the first to incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 16 publications
3
64
0
Order By: Relevance
“…He also developed a more realistic threedimensional FE model of lunate bone to investigate the specific Kienbock's disease [14]. Carrigan et al [15] developed a FE model to study the load transmission into the carpus under static load and concluded to the importance of the cartilage and the rotational degree of freedom of the carpal in the pressure distribution into the wrist. Tarnita et al [16] investigated mechanical parameters (stress and displacements) of a hand phalanx with the FE method under compression, torsion and bending loading, and a comparison with clinical observations of a number of real world hand trauma.…”
Section: Introductionmentioning
confidence: 99%
“…He also developed a more realistic threedimensional FE model of lunate bone to investigate the specific Kienbock's disease [14]. Carrigan et al [15] developed a FE model to study the load transmission into the carpus under static load and concluded to the importance of the cartilage and the rotational degree of freedom of the carpal in the pressure distribution into the wrist. Tarnita et al [16] investigated mechanical parameters (stress and displacements) of a hand phalanx with the FE method under compression, torsion and bending loading, and a comparison with clinical observations of a number of real world hand trauma.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,25,30 Ligament stiffness values for carpal ligaments were assigned from published experimental data, 8,24,31 or from previous computational models in the literature 5,7,16,35 ranging from 40 to 350 N/mm ( Table 1). All carpometacarpal and intermetacarpal ligaments represented in the model were assumed to have a stiffness of 100 N/mm.…”
Section: Model Developmentmentioning
confidence: 99%
“…This is especially true in attempts to model the complexity associated with the wrist joint. A limited number of computational models of the wrist have been created, but all have either restricted the study to two dimensions, 12,16,23,35 restricted the position of the wrist to a static posture, 5,12,18,23,35 or fused bones together to increase computational efficacy. 7 These simplifications decrease computation time and may be justified in various ways, but the native anatomical joint will not function in the same manner as the simplified joint.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations